2011
DOI: 10.3233/ves-2011-0429
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular dysfunction and compensation after removal of acoustic neuroma

Abstract: Objective: To evaluate vestibular function after unilateral acoustic neuroma surgery via a retrosigmoid approach. Methods: Thirty-eight patients were tested using caloric irrigation, static posturography, and the Dizziness Handicap Inventory (DHI) before, and one week to nine months after surgery. Results: Twenty-six patients were categorized as a response group and 12 as a no-response group on the basis of preoperative caloric irrigation findings. The posturographic parameters and DHI scores at one week after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 11 publications
5
15
0
Order By: Relevance
“…We observed that patients with an asynchronous type of response are older or have less preoperative vestibular deficit than those who have an isochronic type of response; this is in agreement with disability after surgery. It has been shown that in patients over the age of 55, compensation will be limited and disability after surgery permanent . In our patients, age is a significant variable because those displaying an asynchronous response were 10 years older than patients who showed an isochronic eye response.…”
Section: Discussionmentioning
confidence: 61%
“…We observed that patients with an asynchronous type of response are older or have less preoperative vestibular deficit than those who have an isochronic type of response; this is in agreement with disability after surgery. It has been shown that in patients over the age of 55, compensation will be limited and disability after surgery permanent . In our patients, age is a significant variable because those displaying an asynchronous response were 10 years older than patients who showed an isochronic eye response.…”
Section: Discussionmentioning
confidence: 61%
“…This vestibular compensation is associated with a postural compensation highlighted by the absence of degradation of postural performance one year after cochlear implantation. As it had been suggested in other kinds of vestibular dysfunction, for example, in the case of vestibular schwannoma, the time-course of implementation of central adaptive mechanisms, characterized by substitution by other sensory afferences and new behavioral strategies, could lead to a recovery of balance control with an improvement in balance performance [ 29 , 30 ], which are close to normal and are difficult to decompensate [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]6,[8][9][10] This process of compensation is not complete with small tumors or in cases of sudden loss of the vestibular functions. 1,2,6,9,[27][28][29][30] Our hypothesis is that continuous firing from irritated vestibular nerves in cases of small VSs hinders the process of central compensation and causes the intractable vestibular symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the larger tumors are associated with better quality of life after surgery due to the well-developed central compensation. 2,4,[8][9][10]15,16,[29][30][31] According to some reports, however, the quality of life after surgery is worse than for the normal population or when nonoperative management is performed. [2][3][4]6,[8][9][10] This process of compensation is not complete with small tumors or in cases of sudden loss of the vestibular functions.…”
Section: Discussionmentioning
confidence: 99%